Developing effective teacher performance - Jones, Jeff, 1950-; Jenkin, Mazda; Lord, Sue.; Sage eBooks (London : Paul Chapman, 2006)
Offering guidance on diagnosing ineffectiveness, supporting ineffective teachers, and procedures when support isn't enough this book is designed to help those teachers who manage others. It explains what under-performance is, and how to develop a school approach to monitoring, supporting and restoring teacher performance.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Teachers -- Rating of -- Great Britain; Teacher effectiveness -- Great Britain; Electronic books